Polar Growth in the Infectious Hyphae of the Phytopathogen Ustilago maydis Depends on a Virulence-Specific Cyclin - Flor-Parra, Ignacio (American Society of Plant Biologists, 2007)
The maize smut fungus Ustilago maydis switches from yeast to hyphal growth to infect maize (Zea mays) plants. This switching is promoted by mating of compatible cells and seems to be required for plant penetration. Although many genes distinctively expressed during this dimorphic switch have been identified and shown to be essential for the infection process, none seems to be explicitly required for polar growth control. Here, we report the characterization of pcl12, encoding a cyclin that interacts specifically with Cdk5, an essential cyclin-dependent kinase with regulatory roles in morphogenesis in U. maydis. Pcl12 fulfills the requirements to be a virulence-specific regulator of polar growth in U. maydis. First, pcl12 expression is induced during the pathogenic development. Secondly, Pcl12 is sufficient to induce hyperpolarized growth in U. maydis cells, as haploid cells overexpressing pcl12 in axenic conditions produce filaments that were morphologically indistinguishable from those produced during the infection process. Finally, cells defective in pcl12 showed impaired polar growth during the formation of the b-dependent filament, the induction of the conjugation tubes, or the formation of a promycelium in spore germination. However, in spite of this pivotal role during morphogenesis, pcl12 mutants were virulent. We discuss the implications of these results for the role of polar growth during the infection process.